Teaching Russian Language to Students from Turkmenistan (Филологический класс, 2021)
At the present stage, the determination of the status of the Russian language, and, consequently, its study in the post-Soviet space is becoming urgent. In the last few years, there has been great interest on the part of the younger generation of the former Soviet republics in obtaining higher education in Russia. In this regard, the problem of Russian language training for foreign applicants entering bachelor’s or master’s degree programs at universities of the Russian Federation is becoming rather urgent. The purpose of the article is to consider the main factors – linguistic and extralinguistic, which hinder the successful teaching of Russian as a foreign language, and to develop methods guides aimed at the formation of the Russian language communicative competence among Turkmen students. The study reveals the extralinguistic (the position of the Russian language in Turkmenistan in the post-Soviet period and at the present) and linguistic (linguistic-phonetical, lexical, grammatical, related to the belonging of the Russian and Turkmen languages to different typological groups) factors that prevent the successful teaching of Turkmen students Russian as a foreign language, and characterizes the psychological and pedagogical specific features of this ethnic group. The authors dwell on the typical mistakes of Turkmen students in the process of interaction of the native and the Russian languages and suggest methods guides for the successful formation of language and speech habits and skills in each of the aspects of the language and in all types of speech. The research materials are summarized in the table, the methods guides can be used in the development of educational complexes not only for the Turkmen audience, but also for representatives of other Turkic-speaking countries. The effectiveness of teaching Turkmen students outside the language environment depends on the following factors: taking into account of the uniqueness of the system of Russian and their native languages; emphasis on the peculiarities of perception and acquisition of these specific features by Turkmen students; systematic purposeful work on phonetics, vocabulary, grammar, types of speech, taking into account the psychological and pedagogical characteristics of the specified contingent of students.